2021
DOI: 10.1007/978-1-0716-1621-5_16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Models for the Study of the Intracellular Activity of Antibiotics

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Considering first antibiotic potency, we observed that Cs was close to the respective MIC (1.5 to 4 x the MIC) in all cases, as previously described in other models of intracellular infection (31,60,61), and independently of the capacity of the drug to accumulate inside monocytes (Table S1) (62,63). This is interpreted as denoting a poor intracellular bioavailability (61). Although gain in potency is a pharmacokinetic-driven parameter, meaning that it essentially reflects a change in the antibiotic concentration needed to reach a specified effect (bacteriostatic effect for Cs (61)), it was not related to the lipophilicity of the antibiotic (Figure S8A).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Considering first antibiotic potency, we observed that Cs was close to the respective MIC (1.5 to 4 x the MIC) in all cases, as previously described in other models of intracellular infection (31,60,61), and independently of the capacity of the drug to accumulate inside monocytes (Table S1) (62,63). This is interpreted as denoting a poor intracellular bioavailability (61). Although gain in potency is a pharmacokinetic-driven parameter, meaning that it essentially reflects a change in the antibiotic concentration needed to reach a specified effect (bacteriostatic effect for Cs (61)), it was not related to the lipophilicity of the antibiotic (Figure S8A).…”
Section: Discussionsupporting
confidence: 85%
“…Considering first antibiotic potency, we observed that Cs was close to the respective MIC (1.5 to 4 x the MIC) in all cases, as previously described in other models of intracellular infection (31,60,61), and independently of the capacity of the drug to accumulate inside monocytes (Table S1) (62,63). This is interpreted as denoting a poor intracellular bioavailability (61).…”
Section: Discussionsupporting
confidence: 82%
“… 1 The avidity of this pathogen to be rapidly internalized by host cells imposes a barrier for commonly used antibiotics, which are more effective in extracellular locations. 2 , 3 Many studies have shown limited accessibility of drugs to the intracellular niche occupied by the pathogen, a factor decreasing their inhibitory activity. 3 In intraphagosomal intracellular pathogens, other factors such the acidity of the compartment colonized by the pathogen can also affect antibiotic activity.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Many studies have shown limited accessibility of drugs to the intracellular niche occupied by the pathogen, a factor decreasing their inhibitory activity. 3 In intraphagosomal intracellular pathogens, other factors such the acidity of the compartment colonized by the pathogen can also affect antibiotic activity. To counterbalance these negative effects, new approaches based on highly penetrating nanoparticles carrying the drug as cargo are currently under intense investigation and development.…”
Section: Introductionmentioning
confidence: 99%